PENGARUH LIVE STREAMING TIKTOK TERHADAP KEPERCAYAAN KONSUMEN PRODUK JIMS HONEY DI SURABAYA DAN DAMPAKNYA PADA KEPUTUSAN PEMBELIAN - Avelia Farera Gabrile Diarya; Veni Rafida (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2023)
This study aims to analyze the effect of Live Streaming TikTok on consumer trust, to analyze consumer trust in purchasing decisions, and to analyze the effect of TikTo Live Streaming on purchasing decisions both directly and indirectly through Jims Honey consumer trust in Surabaya. Various studies have been conducted that social media is an effective marketing place to influence consumer purchasing decisions. Business competition in the current era is very tight, business people are starting to keep abreast of the times and trends in social media. Live Streaming is a good marketing model for selling products while interacting with buyers, with this feature direct consumers in real time. This research was conducted on 102 respondents who had participated in and made purchase decisions via TikTok Live Streaming. This type of research was conducted using explanatory research, with quantitative methods. Furthermore, the data was analyzed using Path Analysis Techniques or path analysis to determine the direct and indirect effects of the variables studied. The results of this study prove that of the four hypotheses found that Live Streaming has an influence on purchasing decisions and has a positive impact on purchasing decisions. As for the amount of direct influence between Live Streaming on purchasing decisions, it is equal to 33.7%, while the indirect effect between Live Streaming TikTok on consumer trust with a magnitude of influence of 0.091 means that the direct effect is greater than the contribution of indirect influence. Keywords: Effect of Live Streaming TikTok, Consumer Trust, Purchase Decision.